Populist political communication: A sociolinguistic study of Dedi Mulyadi's language style on Instagram and YouTube - Tiana Nur Azizah Suparman; Izzuddin Musthafa; Ade Nandang (Direktorat Riset dan Pengabdian kepada Masyarakat UNY, 2026)
This study aims to examine the linguistic practices underlying Dedi Mulyadi’s populist political communication on social media, particularly Instagram and YouTube. It adopts a qualitative approach, employing literature review and content analysis to explore how language is used strategically to construct a populist image and cultural identity. The data consist of videos uploaded on social media, with the analysis focusing on Dedi Mulyadi’s utterances that reflect political communication styles. The researcher serves as the primary instrument, and the data are analyzed using content analysis at the level of discrete units. The findings reveal that Dedi Mulyadi consistently employs Sundanese and Indonesian through language choice, code-switching, and code-mixing, combined with narrative and affective speech styles. This communication style not only reflects his closeness to grassroots communities but also functions as a means of constructing symbolic power and expressing resistance to political elites. These findings underscore the significant role of language in digital spaces in shaping social relations, cultural identity, and effective political communication strategies.